The Study of the effect of planting date on seed quantity and quality yield of clover cultivars - H.R. Danajoo; M. Zamaniyan; Z. Amini (علوم و فناوری بذر ایران)
In order to study the effects of planting date on quantitative and qualitative characteristics of different clover seed varieties, this research was conducted in a field during cropping year of 2012. The research facilities of Seed and Plant Improvement Institute of Karaj use at this study. This research in split plots including the major factor of planting date on 3 cultivation levels (conventional planting date 11 September and delayed planting date including 5 September and 20 October) and the sub-factor clover genotypes at 10 cultivation levels (Persian clover 7 cultivar, Berseem clover (production in Karaj). red clover, a variety called Nasim and Locki clover, a variety called Alborz 1). This research was conducted in a randomized complete block design (RBCD) with four replications. The results showed that the effect of planting date for traits such as grain yield, harvest index and seed quality traits is significant at one percent level. The results seed quality traits showed that the first planting date (11 September) with 86.4 germination percentage and 38.3 germination rate is the best treatment. Comparing the varieties showed that the Persian clover cultivars number 1 with 92.2% germination and 43.8-rate germination is the highest rate. Comparing the mean of varieties showed that the Crimson clover Alborz number 1 seed with 35 grams weight and the harvest index of 4.5 best among the studied varieties